2010
DOI: 10.1007/s12311-009-0153-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Supporting Transfer of Inhibitory Signals into the Spike Output of Spontaneously Firing Cerebellar Nuclear Neurons In Vitro

Abstract: Cerebellar cortical signals are carried to their principal target, the deep cerebellar nuclear neurons (DCNs), via the inhibitory pathway formed by Purkinje cell (PC) axons. Two different intrinsic properties of DCNs, rebound excitation and automatic firing, have been proposed to support ensuing mechanisms for information transfer via inhibitory synapses. The efficacy of these mechanisms was investigated using whole-cell recordings of spontaneously firing DCNs in cerebellar slices. Results using current inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…1e). The maximum rebound frequency of transient or slow rebounds (defined as in [13]) was not significantly different under Bk-Bl (transient rebounds, control 134.5±29.4 Hz, BK-Bl 148±33.1 Hz, n=7, p= 0.066; slow rebounds, control 39.0±5.9 Hz, BK-Bl 38.5± 6.7 Hz, n=9, p=0.868, Fig. 1e).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…1e). The maximum rebound frequency of transient or slow rebounds (defined as in [13]) was not significantly different under Bk-Bl (transient rebounds, control 134.5±29.4 Hz, BK-Bl 148±33.1 Hz, n=7, p= 0.066; slow rebounds, control 39.0±5.9 Hz, BK-Bl 38.5± 6.7 Hz, n=9, p=0.868, Fig. 1e).…”
Section: Resultsmentioning
confidence: 91%
“…Cerebellar slices (275-290 μm) from P15-18C57BL/6 mice were prepared as previously reported [13]. Artificial cerebral spinal fluid contained (in millimolars): 125 NaCl, 2.5 KCl, 1.3 NaH 2 PO 4 , 1.5 MgCl 2 , 26 NaHCO 3 , 20 glucose, and 2.5 CaCl 2 , and was bubbled with 95% O 2 and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…RE has been found in many different neuronal types and is postulated to participate in many functions and brain processes under normal and pathological conditions (Perez-Reyes 2003). Notable examples include the prominent RE of thalamic neurons thought to contribute to sleep and epilepsy (Andersen et al 1964;Kim et al 2001;Steriade and Llinás 1988), the RE found in neurons of circuits generating rhythmic motor outputs (Bertrand and Cazalets 1998;Miller and Selverston 1982;Syed et al 1990), the RE found in neurons of the olfactory and visual pathways (Balu and Strowbridge 2007;Liu and Shipley 2008;Lo et al 1998;Margolis et al 2010), the RE found in the GABAergic periaqueductal gray neurons involved in analgesia (Park et al 2010), and the RE described in neurons of the inferior olive and deep cerebellar nuclei (Aizenman and Linden 1999;Czubayko et al 2001;Jahnsen 1986a;Llinás and Mühlethaler 1988;Llinás and Yarom 1981;Molineux et al 2006;Pedroarena 2010;Pugh and Raman 2006;Tadayonnejad et al 2009;Uusisaari et al 2007) thought important for motor control and other aspects of cerebellar function.…”
mentioning
confidence: 99%
“…However, the amount of hyperpolarization required for a strong rebound might not easily be reached with physiological GABA A inhibition that in CN neurons has been measured to show a reversal potential of about −75 mV [40,41]. Thus, recent physiological studies of rebounds in vivo are conflicting about the possibility and conditions that may trigger rebounds in vivo with some arguing against [42] and others in favor [43][44][45]. Certainly, computational network models that firmly put rebounds in the position to trigger motor behavior [46] are lacking firm experimental backing at this time.…”
Section: Coding Through Rebound Firing In a Compartmental Model Of Cnmentioning
confidence: 99%